Male Trouble - Walsh, F. author. aut Link
VIII, 234 p. 10 illus.
Keywords: A rich analysis of the discourses and figurations of 'crisis masculinity' around the turn of the twenty-first century, working at the intersection of performance and cultural studies and looking at film, television, drama, performance art, visual art and street theatre.